2013
DOI: 10.3109/0142159x.2013.847911
|View full text |Cite
|
Sign up to set email alerts
|

Twelve tips for overnight teaching

Abstract: Preparation for teaching is important in any environment, but understanding the unique timing and circumstances associated with overnight teaching is vital to ensure that overnight teaching is effective. Acknowledging and addressing the physical and cognitive obstacles associated with overnight teaching and learning is necessary to maximize the educational value of overnight teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…15 Importantly, some studies have shown residents perceive less emphasis on education when a night float system is adopted, 13 prompting important dialogue in the literature about how to optimize resident learning during nighttime shifts. 16 We suggest that future studies measuring the impact of changes away from overnight call toward a night float system consistently include educational value as an outcome measure, in addition to the more commonly measured outcomes such as quality of life and duty hour violations. Our data would suggest that transitioning away from overnight call could negatively influence programs’ ability to integrate education and service and future work should examine this issue.…”
Section: Discussionmentioning
confidence: 99%
“…15 Importantly, some studies have shown residents perceive less emphasis on education when a night float system is adopted, 13 prompting important dialogue in the literature about how to optimize resident learning during nighttime shifts. 16 We suggest that future studies measuring the impact of changes away from overnight call toward a night float system consistently include educational value as an outcome measure, in addition to the more commonly measured outcomes such as quality of life and duty hour violations. Our data would suggest that transitioning away from overnight call could negatively influence programs’ ability to integrate education and service and future work should examine this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity of work during out-ofhours shifts can be variable, which creates opportunities with either more time for directed teaching, or learning from clinical cases during busier periods. Following guidance to optimise overnight teaching is advised (Richards et al, 2013).…”
Section: Utilise and Focus On Functioning Servicesmentioning
confidence: 99%
“…Best practices for night‐time teaching include the review of patient lists by faculty members to identify possible teaching opportunities, adding teachable moments when discussing patients (using the techniques described above) and follow‐up with learners the next day, either in person or via electronic contact (i.e. e‐mail) …”
Section: Introductionmentioning
confidence: 99%